2019
DOI: 10.1103/physreva.100.010102
|View full text |Cite
|
Sign up to set email alerts
|

Eternal life of entropy in non-Hermitian quantum systems

Abstract: We find a new effect for the behaviour of Von Neumann entropy. For this we derive the framework for describing Von Neumann entropy in non-Hermitian quantum systems and then apply it to a simple interacting P T symmetric bosonic system. We show that our model is well defined even in the P T broken regime with the introduction of a time-dependent metric and that it displays three distinct behaviours relating to the P T symmetry of the original time-independent Hamiltonian. When the symmetry is unbroken, the entr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 41 publications
2
48
1
Order By: Relevance
“…We show the decoherence characteristics of the spinsystem by studying the entanglement of a two-spin system where the initial state of the system is a maximally entangled state and one of the spin is interacting with the bath. Interestingly, we found that the entanglement in our system persists indefinitely in the entire PTsymmetric regime, unlike the results shown in [34,35], albeit in different settings, which only hold within the spontaneous PT -broken regime and on the exceptional points, respectively.…”
Section: Introductioncontrasting
confidence: 75%
“…We show the decoherence characteristics of the spinsystem by studying the entanglement of a two-spin system where the initial state of the system is a maximally entangled state and one of the spin is interacting with the bath. Interestingly, we found that the entanglement in our system persists indefinitely in the entire PTsymmetric regime, unlike the results shown in [34,35], albeit in different settings, which only hold within the spontaneous PT -broken regime and on the exceptional points, respectively.…”
Section: Introductioncontrasting
confidence: 75%
“…The importance of the authors’ findings of Ref. [ 1 ] lies in the consequences it has to the question of time evolution of non-Hermitian Hamiltonians [ 2 , 3 ], or, more precisely, to the evolution of their associated density matrices. It shows that by introducing an appropriate time-dependent metric, the density matrix of a non-Hermitian Hamiltonian can be linked to one of a Hermitian one by a similarity transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, both share the same von Neumamm entropy. From a practical point of view, Dyson’s formula is an equation of motion that connects the metric and the Hamiltonians that in principle, can be solved as shown in [ 1 ]. On the other hand, the identification in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations